Species of Nemoura (Plecoptera: Nemouridae) from Qinghai, China - Yan, Yanhua; Ma, Cunxin; Yang, Ding; Li, Weihai (Zootaxa, 2022)
A new species of forest stonefly, Nemoura jixiangwangi Yang & Li, sp. nov., is described and compared with related taxa, based on specimens from the Qilian Mountain National Park, Qinghai Province, northwestern China. Nemoura geei Wu, 1929, Nemoura papilla Okamoto, 1922 and Nemoura securigera Klapálek, 1907 are recorded from the province and the mountain range for the first time.